UJI VALIDITAS DAN RELIABILITAS ANGKET KEMANDIRIAN BELAJAR - Isma, Sintia; Sobari, Teti; Yuliani, Wiwin (IKIP Siliwangi, 2023)
Studying is a very important activity for every student. In the learning process, of course, there are principles that must be guided by in order to achieve the learning goals themselves. Self-directed learning is an attitude that every student should have. This is one of the positions that can lead students to success in learning. This is the background to this study. Autonomy in learning can make students independent of others, take initiative in learning, etc. Therefore, it is necessary to develop a measuring tool to determine the level of student autonomy in learning with a tool tested for validity and reliability. A total of 46 claims were found to be valid based on a credibility test using the SPSS application. Then the reliability test got the value 0.908, which means that he is in the highest category. Therefore, based on the validity and reliability of the questionnaire for measuring student autonomy in learning, it can be used for other subjects with variable results.